(untitled) (Palimpsesto, 2017)
This text seeks to establish that the intellectual work was a fundamental mode of resistance within thepolitical prison during the military dictatorship in Chile. This intellectual work had different forms ofexpression. The more notorious form was the creation of schools. Such schools emerged from the talksand conferences that those prisoners with more studies offered to their fellow. Those intellectuals,however, not only gave these conferences, but also devoted their time to the study, the reflection, thewriting and the discussion. In a context of systematic dehumanization, these actions made it posible tohold humanity, or recover it, to gain some kind of control and sustain margins of freedom, as well asgenerating links between prisoners that allowed them to resist and preserve there dignity.